1985
DOI: 10.1029/gl012i005p00287
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric coupling of hydromagnetic waves - Initial results

Abstract: Recently, emphasis in modelling ULF pulsations has begun to shift away from steady‐state driving mechanisms towards impulsive and non‐steady sources. We propose a model allowing numerical solution of the coupled hydromagnetic wave equations with arbitrary azimuthal asymmetry in a cylindrical magnetospheric geometry. General time‐dependent stimuli can be applied at the outer (magnetopause) boundary, an arbitrary Alfvén speed distribution can be defined within the boundary, and ionospheric Joule dissipation is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 11 publications
4
64
0
Order By: Relevance
“…This signature could be present at the fundamental and harmonic frequencies of the field line (assuming these frequencies are present in the fast mode waves), keeping in mind that the position of the turning point of a fast mode wave depends on its frequency, so the cavity-mode frequencies will not obey the simple relation f,= nf•, where f is the frequency, fx is the fundamental and n indicates a harmonic [Samson et al, 1991a]. However, the problem is somewhat complicated because, in reality, a transient frequency is also excited [Allan et al, 1985[Allan et al, , 1986 Whether discretely driven resonances are excited by a cavity mode, a waveguide or some other source, their observation may be distinguished from those driven by stationary broadband sources. In the former case, wave power is observed over a narrow range of L shells, as thin as 0.3 to 0.6 RE in the equatorial plane [Samson and Rankin, 1994].…”
mentioning
confidence: 99%
“…This signature could be present at the fundamental and harmonic frequencies of the field line (assuming these frequencies are present in the fast mode waves), keeping in mind that the position of the turning point of a fast mode wave depends on its frequency, so the cavity-mode frequencies will not obey the simple relation f,= nf•, where f is the frequency, fx is the fundamental and n indicates a harmonic [Samson et al, 1991a]. However, the problem is somewhat complicated because, in reality, a transient frequency is also excited [Allan et al, 1985[Allan et al, , 1986 Whether discretely driven resonances are excited by a cavity mode, a waveguide or some other source, their observation may be distinguished from those driven by stationary broadband sources. In the former case, wave power is observed over a narrow range of L shells, as thin as 0.3 to 0.6 RE in the equatorial plane [Samson and Rankin, 1994].…”
mentioning
confidence: 99%
“…Russel and Hoppe, 1981;Yumoto et al, 1984;Takahashi et al, 1984;Engebretson et al, 1986Engebretson et al, , 1987. Contrarily, a number of investigations using numerical modelling have suggested that cavity or waveguide modes in the magnetosphere are the drivers of the FLRs (Allan et al, 1985;Samson et al, 1995;Waters et al, 2000). A few studies have also presented results in support of the observation of these fast mode resonances (FMRs) in ground-based data (Samson et al, 1995;Menk et al, 2000).…”
Section: Introductionmentioning
confidence: 60%
“…Geophys., 31, 725-743, 2013 www.ann-geophys.net/31/725/2013/ Contrarily, a number of investigators have suggested that FMRs due to cavity or waveguide modes in the plasmasphere are the drivers of the FLRs (Allan et al, 1985;Samson et al, 1995;Waters et al, 2000;Menk et al, 2000). However, clear observational evidence for FMRs is rather limited (Waters et al, 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The time scales of the packeting clearly relate to the described mechanism. Allan et al (1985) and Allan and Poulter (1989) have shown amplitude modulations near a resonance as a result of beating due to the frequency mismatch between the driving cavity mode and the natural Alfve n frequency on one particular ®eld line. In contrary the interaction presented in this work is caused by the frequency mismatch between two azimuthal perturbations on two neighboring ®eld lines.…”
Section: Possible Misinterpretationsmentioning
confidence: 99%
“…The simpli®ed box model approximation was adequate for investigation of further properties of the MHD wave modes, such as temporal development and phase mixing (Pritchett and Dawson, 1978;Inhester, 1987;Southwood and Kivelson, 1990;Mann et al, 1995). More sophisticated models have included the curvature of magnetic ®eld lines, as for example in the cylindrical model (Radoski, 1974;Allan et al, 1985Allan et al, , 1986Allan and Mc Diarmid, 1993), the wave guide model (Rankin et al, 1993;Wright, 1994), and the dipole model Lysak, 1989, 1991a). The latter is used for the simulations presented in this study.…”
Section: Introductionmentioning
confidence: 99%